Relationship between GDP per capita and traffic accidents in Brazilian municipalities in 2005, 2010 and 2015 - Pedro Cisalpino Pinheiro; Renato Azeredo Teixeira; Antonio Luiz Pinho Ribeiro; Deborah Carvalho Malta
ABSTRACT: Objective: The main objective of this paper was to analyze the relation between GDP and three variables linked to traffic accidents in Brazilian municipalities: traffic accident mortality, deaths per vehicle; and vehicles per inhabitant. Methods: 2005, 2010 and 2015 traffic accident (TA) mortality rates were estimated using a three-year moving average and were standardized; then, we applied the empirical Bayes estimator (EBE). Fatality rates (deaths per vehicle) were also based on EBE. The variable vehicles per inhabitant considered the ratio between the fleet and the population at municipal level. For every studied year, we estimated linear regression models between GDP and the interest variables. Results: The variables distribution indicates that, between 2005 and 2015, GDP and vehicles per inhabitant kept the same rising relationship. Fatality rates show a decreasing association with GDP. The distribution of mortality by TA had an inverted U-shaped pattern. The model coefficients practically did not change for the vehicle per inhabitant. Estimated association between deaths per vehicle and GDP kept the same sign, but diminished between 2005 and 2015. Model coefficient sign changed in 2015 for TA mortality. Conclusion: Similar to what was observed in developed countries, the relation between mortality by traffic accidents and GDP changed in the analyzed period.